Moving beyond coal: Exploring and explaining the Powering Past Coal Alliance. (January 2020) - Blondeel, Mathieu; Van de Graaf, Thijs; Haesebrouck, Tim
Abstract: In 2017, the UK and Canada launched the 'Powering Past Coal Alliance' (PPCA), a coalition of governments, organisations and businesses seeking to establish a phase-out of coal for electricity generation by 2050 at the latest. Yet, most of the countries that have signed the charter do not burn coal in large quantities. Some do not even burn coal at all. This raises an important question: Why do countries join such an Alliance? We advance four hypotheses that revolve around material costs, political economy, feedback effects, and identity. We conduct a study of 38 country cases. Through a crisp set Qualitative Comparative Analysis (csQCA) we test which combination of variables explains our outcome of interest (state membership in the PPCA). The results indicate that countries that have no coal in their electricity mix and that have adopted a phase-out plan are most likely to join the PPCA. There are two combinations of conditions almost always lead to the outcome: Countries join the PPCA if they have a phase-out plan and are a climate leader, or they have a phase-out plan and do not have a strong coal industry. Conversely, the solution for non-membership shows that countries do not join the PPCA if they are not a climate leader and do not have a phase out plan, or have a strong coal industry. The results further suggest that the PPCA should focus on different outreach methods, beyond merely expanding its membership, including technical diplomacy and maintaining political momentum at high-level political events.